2016
DOI: 10.1017/s0266467416000535
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of fern-affiliated endophytes in three neotropical forests

Abstract: Abstract:From the saprotrophs that decay plant material to the pathogens and mutualists that shape plant demography at local and regional scales, fungi are major drivers of tropical forest dynamics. Although endophytic fungi are abundant and diverse in many biomes, they reach their greatest diversity in tropical forests, where they can influence plant physiology, performance and survival. The number of quantitative studies regarding endophytes has increased dramatically in the past two decades, but general rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…In other words, if the host tree and its endophytic symbionts are taken to represent what is typical for a broad-leaved tropical tree, it follows that viaphytes are likely commonplace symbionts in the leaves of tropical forests. Other studies that have demonstrated the high abundance of endophytes in tropical forests corroborate this potential ( Arnold & Lutzoni, 2007 ; Rodriguez et al, 2009 ; Thomas et al, 2016 ; Del Olmo-Ruiz & Arnold, 2017 ; Roy & Banerjee, 2018 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In other words, if the host tree and its endophytic symbionts are taken to represent what is typical for a broad-leaved tropical tree, it follows that viaphytes are likely commonplace symbionts in the leaves of tropical forests. Other studies that have demonstrated the high abundance of endophytes in tropical forests corroborate this potential ( Arnold & Lutzoni, 2007 ; Rodriguez et al, 2009 ; Thomas et al, 2016 ; Del Olmo-Ruiz & Arnold, 2017 ; Roy & Banerjee, 2018 ).…”
Section: Discussionsupporting
confidence: 52%
“…2). While this pattern is typical for culturable studies of leaf endophytes (Arnold et al, 2000Vega et al, 2010;Gazis & Chaverri, 2010;Ikeda et al, 2014;Del Olmo-Ruiz & Arnold, 2017), some patterns in the data suggest that they are partly due to methodological biases. For instance, Penicillium spp.…”
Section: Viaphyte Prevalencementioning
confidence: 84%
“… WB5133 KY940500 Ophioceras sp. F2224 (KU747946) 69 94 Stem 2.22 Ascomycota; Sordariomycetes; Magnaporthales Magnaporthales WB5119 KY940487 OphiostomatalesF1732 (KU747803) 69 97 Stem 2.22 Ascomycota; Sordariomycetes; Ophiostomatales Ophiostomatales WB5134 KY940501 Microsphaeropsis sp. S4A1ACS (KY305064) 70 99 Root 0.53 Ascomycota; Dothideomycetes; Pleosporales Microsphaeropsis sp.…”
Section: Resultsmentioning
confidence: 99%
“…). While some studies have found evidence for species specificity of fungal endophytic communities in plant leaves (Wearn et al., ; Del Olmo‐Ruiz and Arnold, ), others have not (Higgins et al., ). Our results suggest that evidence of host specificity in endophytic communities in some studies (but not others) could be due in part to the magnitude of differences in hosts’ chemistry that differentially promotes dominant members of the fungal microbiome (Arnold et al., ).…”
Section: Discussionmentioning
confidence: 99%